2021
DOI: 10.1111/gcb.15503
|View full text |Cite
|
Sign up to set email alerts
|

The rise of novelty in marine ecosystems: The Baltic Sea case

Abstract: Global environmental changes have accelerated at an unprecedented rate in recent decades due to human activities. As a consequence, the incidence of novel abiotic conditions and biotic communities, which have been continuously emerging in the Earth system, has rapidly risen. Despite growing attention to the incidence and challenges posed by novelty in terrestrial ecosystems, novelty has not yet been quantified in marine ecosystems. Here, we measured for the rate of novelty (RoN) in abiotic conditions and commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 117 publications
0
18
0
Order By: Relevance
“…1971-2013 (Törnroos et al, 2019). First-time observations of known fish species in sub-basins where they were not previously caught have been related to increasing spring temperatures (+3-6 °C during 1980-2015; (Ammar et al, 2021). Such potential temporal patterns were not analyzed here, where we merged the fish incidence data across years to narrow down likely SR estimates for different sub-basins and focused on large-scale spatial patterns.…”
Section: Discussionmentioning
confidence: 99%
“…1971-2013 (Törnroos et al, 2019). First-time observations of known fish species in sub-basins where they were not previously caught have been related to increasing spring temperatures (+3-6 °C during 1980-2015; (Ammar et al, 2021). Such potential temporal patterns were not analyzed here, where we merged the fish incidence data across years to narrow down likely SR estimates for different sub-basins and focused on large-scale spatial patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The marine food webs of the Baltic Sea have been, and are projected to be, impacted by climate change-related variables by altering the physical environment for several species, by impacting microevolution of species in the Baltic Sea, and by synergistic effects of climate change and other environmental drivers such as eutrophication and hypoxia (Niiranen et al, 2013;Wikner and Andersson, 2012;Schmidt et al, 2020;Pecuchet et al, 2020;Ehrnsten et al, 2020). It has even been shown that the entire ecosystem may fulfil criteria for becoming a novel system with profoundly altered energy-pathways (Ammar et al, 2021). Below, recent findings regarding specifically climate impacts on trophic structure and functioning on the Baltic Sea ecosystem are summarized.…”
Section: Climate Change and Ecosystem Structure And Functionmentioning
confidence: 99%
“…Earlier studies indicate that climate change, eutrophication, and overfishing, have resulted in structural and functional changes of food webs (Pecuchet et al, 2019;Törnroos et al, 2019), and ecosystem regime shifts in different parts of the Baltic Sea (e.g., Möllmann et al, 2009;Lindegren et al, 2012;Olsson et al, 2015;Eklöf et al, 2020). Recently, it has been found that novel biotic and abiotic conditions have increasingly appeared in the Baltic Sea in the past decades (Ammar et al, 2021). Future Baltic Sea projections indicate large increases in seawater temperature, decreases in salinity (Meier et al, 2012;Andersson et al, 2015;Saraiva et al, 2019) with severe changes in species and food-webs (Niiranen et al, 2013;Bauer et al, 2018Bauer et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%